(untitled) (Fiep Bulletin - online, 2014)
Historically we observe that the search for the success is the main objective of the systemize education. The error was placed as something to be prevented, therefore it is seen as an imperfection of the pupil. It is about one of the elements of the learning process. In this text, by means of the comment of children between six and eight years old, in lessons of Physical Education we consider a reflection concerning the error. During much time this disciplines was oriented exclusively for Biological Sciences, occupying with the questions of the hygiene, the physical preparation and the income technician of the pupils so that they took care of to the standards of the sport of high level. Considering such objectives, the error he was something to be prevented. Currently the Physical Education occupies with the construction and understanding of the motricity of its pupils. Thus, it becomes imperative to investigate the process of conscience taking, therefore the error has decisive participation, helping the pupil the understand his motor action. It fits to the professor to use it to provoke, together the pupils, cognitve conflicts, taking them to elaborate it and to test hypotheses regarding the situation faced during the lesson. This process will be able to provide the taking of conscience of the actions of the pupils and, in the specific case of the Physical Education, of its motor action. It is treated then, the conscience taking, of relearning, in the plan of the thought, what already it learns in the plan of the action. Therefore, the error does not have to be neglected, but really understood as one of the components of the learning in the education systemize and specially in the Physical Education.